Getting started with ethereum : a step-by-step guide to becoming a blockchain developer - Bauer, Davi Pedro (Apress, 2022)
Get started with blockchain development with this step-by-step guide. This book takes you all the way from installing requisite software through writing, testing, and deploying smart contracts. Getting Started with Ethereum delves into technologies most closely associated with Ethereum, such as IPFS, Filecoin, ENS, Chainlink, Truffle, Ganache, OpenZeppelin, Pinata, Fleek, Infura, Metamask, and Opensea. Author Davi Bauer walks you through project creation, how to compile projects and contracts, configure networks, and deploy smart contracts on blockchains. He then covers smart contracts, including deploying and verifying them. This book approaches blockchain in a way that allows you to focus on the topic that most interests you, covering Ethereum-related technologies broadly and not just focusing on Solidity. This hands-on guide offers a practical rather than conceptual approach get you coding. Upon completing this book, you will be able to confidently develop and deploy smart contracts on blockchains. Source code can be found at https://github.com/Apress/getting-started-ethereum. What You Will Learn Understand tokenization of assets, including NFTs, using Ethereum Host censorship-resistant applications using IPFS Deploy on second-layer blockchains using Polygon Deploy smart contracts with multiple technologies around Ethereum Who Is This Book For Off-chain developers who want to migrate to on-chain development starting with the Ethereum blockchain and the technologies around it. Prior programming knowledge and conceptual understanding of blockchain is necessary.